PENDEKATAN FILOSOFIS PSIKOLOGI PENDIDIKAN SEBAGAI UPAYA PENCAPAIAN TUJUAN PEMBELAJARAN KESENIAN SEKURA DI SD TUNAS MEKAR INDONESIA, BANDAR LAMPUNG - ANGGRAINI, DIAN (Universitas Islam Negeri Raden Intan Lampung, 2018)
Sekura art is one of the arts that undergo development based on the occurrence of switching function. Based on the implementation there are two types sekura division, namely Sekura Kecah or Clean and Sekura Sekura Sekura Kamak or Kotor. Currently Sekura art has become a folk art tends to be familiar with the Lampung people because always present in any custom events, the celebration of Eid, and even be used as teaching materials in some of Elementary School (SD) Bandar Lampung. The learning of sekura art at SD Tunas Mekar Indonesia, Bandar Lampung was used as the focus of the research. The expected learning objectives are the development of student character that is adjusted to his age. In this case the embedded character expected of students who love the country, respect, honor, love, and care for others and the surrounding environment. In addition it is expected also embedded creative and innovative soul that is accompanied by a sense of responsibility is also hard work. It is pursued through philosophical approach of educational psychology. The results of this study is to instill the character of students in elementary Tunas Mekar Indonesia, Bandar Lampung, which is expected to be realized through arts learning tends to be effective sekura do with a philosophical approach to educational psychology.